Pengembangan model laboratorium dalam pendidikan ekonomi - Nuzulul (PT. Anagata Sembagi Education, 2024)
A laboratory is a requirement required by all study programs to support the smooth learning process, including the Economic Education study program. In this research, the author used a research method known as library research, namely a series of activities that are in line with the data collection methodology. Laboratory-based education helps students understand concepts more easily, facilitates understanding of the material presented to them, strengthens understanding of related material, and develops critical thinking skills.